Gestão e processos participativos: possibilidades e limites na organização e funcionamento de conselhos escolares na estância hidromineral de Poá - Soares, Carolina de Queiroz Silva (2021)
This paper aims to analyze the organization and functioning of the School Councils in two schools of the municipal network of the Hidromineral Resort of Poá, located in Greater São Paulo. The investigation seeks to answer the following question: What elements affect the organization and functioning of the School Council, for collective decision-making in the school space? In other words, words sought to apprehend the view of management teams on the functioning of school councils, and the sharing of decisions between school actors. The choice of the object of study is justified by the company in being able to collaborate to broaden the understanding of the mechanisms of Democratic Management, considering that the School Council is a collegiate body whose main function is to contribute to decision-making shared among the actors schoolchildren. The theoretical foundation was supported by studies dealing with Democratic Management in public education and collegiate bodies, with an emphasis on the School Council. This is a qualitative investigation, which uses documentary analysis and semi-structured interviews. An analysis of data revealed in relation to official documents, in particular the National Program for the Strengthening of School Councils, a municipal education network of the Hidromineral Resort of Poá does not use them. With regard to information, respondents pointed out that the choice of School Council members is based on internal and external legislation, however, the data indicates that the actions promoted by the School Council are based on administrative and financial matters, to the detriment of pedagogical issues. The data also indicate the need to expand the discussion in the municipal education system on the strengthening of School Councils, considering the relevance of this collegiate body for the improvement of the school's democratic management mechanisms.